Knowledge and attitude on environmental disasters through social media among university students in selected universities in Selangor, Malaysia - Sazali, Sarah Aina; Abdul Rahman, Haliza; Abu Bakar, Azrin Shah (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2023)
Introduction: Social media is one of the best platforms to swiftly obtain news and information, particularly among young adults. This study aimed to determine the level of knowledge and attitude on environmental disasters through social media among university students in Selangor, Malaysia. Methods: A cross-sectional study was conducted to determine the knowledge and attitude towards environmental disasters through social media among university students in selected universities in Selangor, Malaysia. A set of self-administered questionnaire with a close-response format was distributed online. Results: WhatsApp was the highest used social media at public university (49.1), and private university (49.8). The level of knowledge in public university (87.0) and private university (66.7) was moderate, while the attitude level of students at both universities was also moderate; public university (65.6) and private university (81.1). There was a significant difference between public and private university in knowledge (p<0.05, p=0.012) and attitude (p<0.05, p=0.029) towards environmental disasters through social media. Additionally, there was also a significant difference between ethnicity in regards to knowledge (p<0.05, p=0.013) and attitude (p<0.05, p=0.026) in both universities. Conclusion: There was a significant difference in knowledge and attitude towards environmental disasters through social media between public and private university. The awareness among students must be increased through frequent educational programs such as campaigns, workshops, and exhibitions on environmental disasters. Continuous educational methods can also be done through other initiatives such as introducing environmental disasters in the syllabus as a mandatory elective course in the university.